Upstairs girls : prostitution in the American West - Rutter, Michael, 1953- (Farcountry Press, 2005)
"Discusses the history of prostitution in the American West, including: the moral purity movement, madams, Chinese sex trade, prostitutes who followed the railroad, mining camps, and military posts. Offers profiles on 14 prostitutes and madams"--Provided by publisher.